What is an Accountant? An Investigation of Images. Issue 5 (20th October 2019) - Caglio, Ariela; Cameran, Mara; Klobas, Jane
Abstract: The purpose of our paper is to identify different images of accountants held by different groups of people and to understand how the different images come about. In doing so, we focus on how accountants are perceived by others as well as how they perceive themselves. Through analysis of 1, 794 usable questionnaire responses by university students, newly appointed accountants, and practicing accountants, we find an image close to the beancounter stereotype, and that of a modern professional, with the highest score for success but also for honesty. We also uncover a third image including nuances that are neither favorable nor unfavorable (the plain vanilla accountant), which suggests that the extremes found in cultural representations do not always reflect the real world. In addition, we find that the greater the distance from the profession, the less attractive the image of accountants is and that different sources of influence affect perceptions of accountants. In particular, the public perception of an accountant is less favorable when constructed from media sources. Finally, we add to the existing literature by showing that the self-image of accountants may change over time as experienced practitioners, compared to new hires, exhibit a sort of disillusionment about their professionalism.